Review of the literature about Thymic Carcinomas - Mona Mlika; Faouzi Mezni (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2017)
Background: Thymic carcinomas (TC) are rare tumors with challenging diagnosis and management. We aimed to describe the clinical and microscopic characteristics of TC through a literature review. Results: 82 articles and abstracts were retained about 2913 TC. Our study contained 1760 men and 1153 women with a mean age of 55.32 years. The delay of diagnosis was specified in 10 cases and varied between 8 months and 2 years. Symptoms consisted mainly in chest pain and dyspnea. The Computed Tomography-scan  (CT-scan) findings  were  specified  in  63  cases.  Microscopic findings  were  noticed  in 1766  cases.  They  consisted  mainly  in  squamous  cell  carcinoma  in  1297  cases  and  undifferentiated carcinoma in 239 cases. The patients presented stage 1 tumors in 165 cases, stage II in 362 cases, stage III in 1011 cases and stage IV in 1166 cases. The treatment modalities were noticed in 2803 cases. There was no consensus of the regimen of chemotherapy or the place of the radiation therapy but all studies highlighted the key role of the complete surgical resection when possible. Conclusion: Our  results  highlight  the  lack  of  consensual  management  of  TC.  The  chemotherapy regimen,  the  second-line  chemotherapy  and  the  indications  of  radiation  therapy  seem  non-consensual and  need  further  studies.  Many  interrogations  remain  concerning  the  management  of  these  tumors according  to  their  histologic  grade.  The  real  place  of  targeted  therapy  remains  to  assess  and  the  rare opinions published are based on rare and non-representative cases.